Modelling Adoption of Innovation at a State Owned Company - Tamara Latifah Jasmine; Tatang Akhmad Taufik (IPTEK Journal of Proceedings Series, 2020)
This study aims To measure the level of technology readiness level (TRL) and to assess user acceptance to use the transportation management system software utilizing technology acceptance model (TAM) approach. Technology acceptance model (TAM) is used to describe the three components, i.e., perceived usefulness, perceived ease of use, and behavioral intention to use . To ensure that these 3 components are important factors of TAM, authors utilized factor analysis method, whereas t-test calculations were carried out to find out the relationships between components. The results show that the TRL of transportation management system software readiness is 9 which means that it is ready to be used widely in the company. The factor analysis shows that TAM is influenced by the three components, which is able to explain about 66.8% of variations. In the meantime the t test shows that all hypotheses are accepted, so there are significant relationships between components analyzed. To summarize, the authors conclude that the company can benefit the usefulness and ease of use of the transportation management system software developed, so that the behavioral intention to use and the utilization of this technological innovation can be optimized.